2014
DOI: 10.1002/vnl.21413
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinyl chloride)/single wall carbon nanotubes composites: Investigation of mechanical and thermal characteristics

Abstract: Composites of polyvinylchloride (PVC) with single wall carbon nanotubes (SWCNTs) were prepared by plastisol curing. Scanning electron microscopy (SEM) observations revealed that appropriate dispersion of the nanotubes was achieved. The mechanical properties showed that SWCNT improved the Young's modulus and tensile strength of the PVC. The composites have higher elongation at break and toughness as well. By comparing the mechanical properties of the composites, it is found that there is a critical SWCNT loadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 34 publications
4
12
0
Order By: Relevance
“…These factors resulted in good interaction between the functionalized nanotubes and the PVB matrix, and consequently, better stress transfer from the polymer to the filler was created. The obtained results also showed that similar to the our previous study and other reports, there was a critical nanotube loading in the PVB matrix, below which the reinforcing effect for nanocomposites increased with increasing nanotube content. This critical point for the f‐SWCNTs in this study was about 0.9 wt %.…”
Section: Resultssupporting
confidence: 91%
“…These factors resulted in good interaction between the functionalized nanotubes and the PVB matrix, and consequently, better stress transfer from the polymer to the filler was created. The obtained results also showed that similar to the our previous study and other reports, there was a critical nanotube loading in the PVB matrix, below which the reinforcing effect for nanocomposites increased with increasing nanotube content. This critical point for the f‐SWCNTs in this study was about 0.9 wt %.…”
Section: Resultssupporting
confidence: 91%
“…The SEM image for the PVC/SWCNT showed that the carbon nanotubes generated bridges in cracks and, consequently, improved the mechanical and thermal properties of the composite. This has been reported in our previous works . These bridges could act as an obstacle for plasticizer migration.…”
Section: Resultssupporting
confidence: 79%
“…SWCNTs have a high thermal conductivity, which dissipates heat in polymers. Also, the absorption of chlorine on carbon nanotubes has been reported …”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Zanjanijam et al 16 observed a progressive increase in the tensile strength of SWNT/PVC composites as the nanotube content was increased from 0,25 to 0.75%, however in composites with higher nanotube contents the tensile strength was practically the same as PVC unmodified. The authors attributed this increase in tensile strength to the adequate dispersion of the nanotubes in the polymer matrix in composites containing up to 0.75% of nanoparticles, however the poor dispersion of higher nanotube contents maintains the tensile strength unchanged in relation to the isolated polymer.…”
Section: Resultsmentioning
confidence: 96%